SOCIAL MEDIA IN THE WORKPLACE - Appignani, Timothy; Jones, Steve; Watson-Manheim, Mary Beth; Welch, Eric (AoIR Selected Papers of Internet Research, 2015)
Though social media usage crosses the spectrum of age, race, and occupation there are still prohibitions about its use in the workplace. Our research maps the relationship between workers and their use of social media, for work and personal purposes based on results from a completed survey of 3,000 non-faculty staff at a large Midwestern university.